Industrie 4.0 implementation challenges in Germany - Azizov, Azizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: This article examines the problems and challenges of the implementation of Industry 4.0 in Germany, focusing on the technological, economic, and social aspects of this industrial transformation. Special emphasis is placed on the "Industrie 4.0" policy in Germany, which has been a key driver of this transformation. The discussion is organized around three key areas: technological and economic challenges, social and ethical challenges, and future directions. As a result, it was concluded that countries need to adopt a long-term strategic plan to successfully meet the requirements of Industry 4.0. The author outlines 5 solution in order to implement "Industrie 4.0": strengthening cybersecurity measures, promoting investment in digital infrastructure, supporting workforce development and reskilling, encouraging innovation and collaboration, enhancing international cooperation.